European neighbourhood policy: the eastern partnership. A decalogue of differentiation and reform proposals - Podadera-Rivera, Pablo; Calderón-Vázquez, Francisco José (My University, 2015)
We could consider that the neighborhood policy of the EU begins to take shape from the very moment that Robert Schumann and Jean Monnet announced the intention to create an economic community of coal and steel. However, it gains special relevance from May 1, 2004, when the biggest enlargement known until the European Union took place. This paper aims to contribute to the debate on the review of the European Neighbourhood Policy in the framework of the EU consultation on the future of its relations with neighboring countries, launched on March 4, 2015.
Keywords: Unión Europea -- Adhesión; Differentiation; Unión Europea; European neighbourhood policy; Eastern partnership